ANALISIS PERDAGANGAN INTRA INDUSTRI SEKTOR MANUFAKTUR: STUDI KASUS ASEAN-5 - Diah Wahyuningsih (MediaTrend, 2011)
Research analyzes the Intra industry Trade in Manufacture Sector between Indonesia and other countries such as Malaysia, Singapore, Thailand and Philippines. It also analyzes the relationship of industrial sectors in the economic field, especially among countries at ASEAN-5. The intra industry trade is measured based on Grubel-Lloyd Index with the aggregation rate of three digits in the ISIC (International Standard Industrial Classification). Panel data analysis tool is employed to analyze the factors influencing intra industry trade. Result of research indicates that the intensity of the intra industry trade between Indonesia and ASEAN-4 is relatively higher and consistent with that during 1998-2007. The dominant product in the intra industry trade is iron and steel metals. Market structure, product differentiation, and foreign investment, positively and significantly, influence the intra industry trade between Indonesia and ASEAN-4 countries. Machinery, equipment, and electric tool industry is the highest-rank sector based on its forward linkage coefficient. The machinery, equipment, and electric tool industry sector is important to support the growth of other sectors. With respect to the direct backward linkage coefficient, the sector with highest coefficient is the base industry of iron and steel. It shows that base industry of iron and steel sector gives enough great contribution to other sector.